FENOMENA DAKWAH RADIKAL: PENYIKAPAN AKADEMISI STAIN SAS BABEL TERHADAP MODEL DAN PENDEKATAN DALAM BERDAKWAH - Basri Basri (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
This article is focused on a description of how a group of academicians deals with radicalism in Islamic preaching (dakwa). The main problem is basically related to shifting paradigm in conveying religious message. The paradigm emerges in form of fundamentalism, extremism, radicalism and disappearance of belief and tolerance towards other people of different religious adherences.Some models and approaches of dakwa exercised by Islamic preachers are variousand therefore need preachers’ commitment, creativity, knowledge, skills, time allocation, etc. As preachers, academicians of STAIN SAS Babel should fulfill such requirements and qualifications. One of the models performed by STAIN’s academicians is dakwa bi al-hal (dakwa by practicing). The academicians write their religious views and understanding in books, journals and newspapers, attending scientific meetings and discussions, and involving in community empowerment programs. In addition, the academicians also use a phenomenology approach in which religious doctrine and understanding are clearly explained and comprehended to cope with social problems. By doing so, the academicians hope that people of Bangka Belitung could live peacefully and harmoniously whatever their religious belief and practice.